Crescimento da Araucaria angustifolia regenerada sob Pinus elliottii e em povoamento homogêneo interplantado com Pinus spp. - Soligo, Artur José (2009)
born free, independent of the considerate age. Being treated of the youngest natural regeneration (height < 1,80m) or of the araucarias higher ages, (height > 1,80m), the factor that determined the stoppage or retaking of the growth in height was the effect of the competition exercised by the adult settlement of the pinus. The retaking of the growth in height happened after the shallow cut of the pinus and consequent liberation of the regeneration of the araucaria the light. Without this condition, the natural regeneration of araucaria, stays as bank of plants, like happens at a native forest, outstanding factor to the trees (238 and 1312), that stayed as bank of plants until nine years old, reaching heights of 2 meters. The recruitment always happened near the age that openings were proceeded in the pinus settlement. The morphometric study showed that diameter and height presented strong and positive correlation with the area and the top length. The height showed correlation with the age. In the study of the growth of the araucarias in the experimental area two, characterized by the maintenance of the dominated trees, after the accomplishment of the rough-hewing, six trees were selected, two in each position of ground (inferior, medium and superior position), considering the existence of similar competition indexes exercised by the inter-planted pinus. With the pairs of data of ANATRO, were made studies of the growth of the height and of the diameter in function of the age. The model of Gram was defined to describe the growth of the height in function of the age and the model of Backmann for the diameter. The analysis of the periodic increment in height of the dominated araucarias showed ascending increments until the 15th year. After, the increments they were very reduced for a period of 20 years, motivated by the competition and closing of the dossal of the dominant trees. With the rough-hewing of the dominated araucarias, it happened the retaking of the growth in height in a significant way only in the last four years, when the percentile increment in height passed from 0,5% to 1,9%. The medium annual increment in diameter presented the same height tendency, but with immediate retaking after the liberation, passing from 0,11cm to 0,23cm sc. The sample trees presented high relationship h/d in the order of 87 and a reduced top height =1,70m.